Analysis of The Human Musculoskeletal System Concept in Goyang Karawang Dance as a Learning Resource - Eka Siti Barkah; Suyitno Aloysius; Paidi (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the integration of the traditional Goyang Karawang dance (GoKar) into biology education, particularly in teaching the human musculoskeletal system. Using a qualitative case study approach informed by ethnobiological and ethnopedagogical frameworks, data were collected through performance observations, interviews with dance artists and high school biology teachers, and document analysis. The analysis focused on the biomechanics and socio-cognitive meanings of core GoKar movements. Findings reveal that the dance involves coordinated actions of key muscle groups and joints, such as agonist-antagonist pairs and postural control centered in the hip and shoulder areas. Simultaneously, each movement expresses cultural values of grace, confidence, and balance, reflecting Sundanese philosophies of harmony. These embodied elements connect scientific anatomical knowledge with students’ lived cultural experiences. The research contributes to culturally responsive pedagogy by offering an experiential learning model that supports conceptual understanding while reinforcing local wisdom as a valid epistemic resource. This integration aligns with the goals of Indonesia’s Merdeka Curriculum and the Profile of Pancasila Students, promoting critical thinking, autonomy, and appreciation of cultural diversity. Overall, the study offers a transdisciplinary approach to science education that is inclusive, contextual, and pedagogically meaningful.